Needs Analysis for the Development of Readiness-Based Differentiated English Writing Materials - Sakina Simal; Sari Hidayati (Universitas Islam Negeri Palopo, 2026)
Many English writing materials are designed for heterogeneous classrooms without adequately considering differences in students’ writing readiness levels. Therefore, this study aims to analyze students’ needs as a basis for developing readiness-based differentiated English writing materials. Readiness-based differentiation is an approach that adapts content, process, and product to students' readiness levels. The novelty of this study lies in integrating needs analysis with readiness-based differentiation to inform the development of English writing materials. A mixed-methods design was employed involving 26 eighth-grade students and one English teacher from an Indonesian junior secondary school. Data were collected through student questionnaires, semi-structured interviews, and writing tests. The findings revealed variations in students’ writing readiness levels within the same classroom. In addition, students demonstrated different learning needs according to their readiness levels. Furthermore, students required English writing materials focusing on descriptive texts with topics relevant to their daily lives, clear instructions, visual support, and collaborative learning activities supported by scaffolding. These findings provide an empirical foundation for developing readiness-based differentiated English writing materials tailored to students' needs and contribute to more effective differentiated English writing instruction at the junior secondary school level.